Exhaled Breath Aerosol Shedding of Highly Transmissible Versus Prior Severe Acute Respiratory Syndrome Coronavirus 2 Variants. (26th October 2022) - Lai, Jianyu; Coleman, Kristen K; Tai, S H Sheldon; German, Jennifer; Hong, Filbert; Albert, Barbara; Esparza, Yi; Srikakulapu, Aditya K; Schanz, Maria; Maldonado, Isabel Sierra; Oertel, Molly; Fadul, Naja; et al.
Abstract: Background: Aerosol inhalation is recognized as the dominant mode of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission. Three highly transmissible lineages evolved during the pandemic. One hypothesis to explain increased transmissibility is that natural selection favors variants with higher rates of viral aerosol shedding. However, the extent of aerosol shedding of successive SARS-CoV-2 variants is unknown. We aimed to measure the infectivity and rate of SARS-CoV-2 shedding into exhaled breath aerosol (EBA) by individuals during the Delta and Omicron waves and compared those rates with those of prior SARS-CoV-2 variants from our previously published work. Methods: Individuals with coronavirus disease 2019 (COVID-19) (n = 93; 32 vaccinated and 20 boosted) were recruited to give samples, including 30-minute breath samples into a Gesundheit-II EBA sampler. Samples were quantified for viral RNA using reverse-transcription polymerase chain reaction and cultured for virus. Results: Alpha (n = 4), Delta (n = 3), and Omicron (n = 29) cases shed significantly more viral RNA copies into EBAs than cases infected with ancestral strains and variants not associated with increased transmissibility (n = 57). All Delta and Omicron cases were fully vaccinated and most Omicron cases were boosted. We cultured virus from the EBA of 1 boosted and 3 fully vaccinated cases. Conclusions: Alpha, Delta, and Omicron independently evolved high viral aerosol shedding phenotypes, demonstrating convergent evolution. Vaccinated and boosted cases can shed infectious SARS-CoV-2 via EBA. These findings support a dominant role of infectious aerosols in transmission of SARS-CoV-2. Monitoring aerosol shedding from new variants and emerging pathogens can be an important component of future threat assessments and guide interventions to prevent transmission. Abstract : Highly transmissible variants (Alpha, Delta, and Omicron) demonstrate greater viral aerosol shedding phenotypes compared with prior variants, consistent with a dominant role for airborne transmission of COVID-19. Fully vaccinated and boosted individuals infected with SARS-CoV-2 can shed infectious viral aerosols.